Survival and developmental competence of bovine embryos at different developmental stages and separated blastomeres after vitrification in different solutions. (30th August 2017) - Juanpanich, Theesit; Suttirojpattana, Tayita; Takayama, Mari; Liang, Yuanyuan; Dochi, Osamu; Parnpai, Rangsun; Imai, Kei
Abstract: Generating techniques to enhance the success of blastomere separation is important for bovine economy, because it increases the number of transferable embryos. This study aimed to identify the optimum cryoprotectants for the vitrification of bovine embryos and the separation of blastomeres at different stages. In experiment 1, expanded blastocysts were vitrified in two different vitrification solutions, either (1) ethylene glycol (EG) + propylene glycol (PG) or (2) EG. The survival rate of blastocysts in the EG + PG was higher than that of the EG. In experiment 2, intact two‐cell and eight‐cell stage embryos were vitrified in the same solutions used in experiment 1. The EG + PG produced more dead embryos than the EG ( P < 0.05). In the EG, the rate of blastocyst formation was similar for the vitrified two‐ and eight‐cell embryos and the non‐vitrified ywo‐cell embryos. In experiment 3, separated blastomeres of two‐ and eight‐cell embryos were vitrified in EG. There was no difference in the rate of blastocyst formation and total number of cells between the two vitrified groups. In summary, at the blastocyst stage, EG + PG was superior, based on both survival rates and cell numbers; however, at the 2–8 cell stage, the use of EG alone was better than the other groups.